Evaluation of cases of infertility by diagnostic laparoscopy - Wankhede, Sachin; Thakare, Sarika; Goverdhan, Nivedita; Shahane, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility affects nearly 10-15% of couples and is an important part of clinical practice. Leading causes of infertility include tubal disease, ovulatory disorders, uterine or cervical factors, endometriosis and male factor infertility. The objective of the study was to find out different causes of female infertility with diagnostic laparoscopy. Methods: This was a descriptive study conducted from February 2012 to November 2013. 115 patients with infertility attending the infertility clinic in OPD of Obstetrics and Gynaecology were evaluated clinically with detailed history. The necessary investigations were carried out and the laparoscopic findings were documented. Results: There were 91 cases (79.13%) with primary infertility and 24 (20.87%) with secondary infertility. Laparoscopy revealed normal findings in 14 cases (15.38%) of primary infertility and 1 case (4.17%) of secondary infertility. Pelvic abnormality was found in 100 cases (86.95%). Tubal block was the most common pathology found in 36 cases (31.30%) followed by polycystic ovaries in 32 (27.83%) and adhesions in 24 (20.87%). Uterine anomalies were found in 3 cases (3.30%). Conclusions: Diagnostic laparoscopy is a valuable technique and a mandatory investigation, which, though invasive, is more convenient and more precise for the diagnosis of infertility. Because of its potential diagnostic as well as therapeutic benefits, all patients with infertility should undergo diagnostic laparoscopy as part of their primary workup of infertility.